We burn or bury….! why not donate? A comparative study on barriers of organ donation among medical and non-medical students in Puducherry - Jagadeeson, Barathalakshmi; Sheela Jayabalan, Jaya; Radjasegarane, Arulprasad; Sureshbabu, Sriram (International Journal Of Community Medicine And Public Health, 2021)
Background: Organ transplantation is an effective medical care for end- stage organ failure. Health professionals play an important role in raising awareness, motivating, and subsequently increasing the organ donation rates In India, "The Transplantation of Human Organs Act" was legalized in 1994. Yet, organ donation rate in India is very poor (0.34 per million) compared to developed countries. This study was done with the aim to identify the barriers of the organ donation among Medical and Non-Medical students and to compare the Knowledge, awareness and attitude towards donation among Medical and Non-Medical students. Methods: This is a cross sectional study carried out in two months duration, by the Department of Community Medicine, Sri Lakshmi Narayana Institute of Medical Sciences, Puducherry. Results: Among the 400 participants, 76 percent of students were aware of organ donation, out of which highest awareness (100%) among medical students and lowest (54%) were among arts and science students. Among the four streams, nursing and allied health science students reported better knowledge score of (11.09±2.18), whereas arts and science students reported a lower score of (8.94±2.73), p- value <0.05. Conclusions: The attitude and practice towards organ donation were similar among all streams of students. But the students related to medical field had a better awareness and knowledge compared to non-medical students.